Pengaruh Lingkungan Eksternal, Kompetensi Sumber Daya Manusia Dan Knowledge Management Terhadap Kinerja Organisasi Dengan Inovasi Sebagai Variabel Mediasi (Studi Pada UMKM di Kelurahan Pagerharjo, Kabupaten Kulon Progo) - Panuji, Albertus Veri Astu; Ernawati, Maria Theresia; Poerwanto, Gregorius Hendra (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2024)
This study aims to investigate the relationships between the external environment, human resource competencies, knowledge management, and organizational performance with innovation as a mediating variable. Data were collected through direct distribution of questionnaires to 60 respondents who are stakeholders of Kalurahan Pagerharjo, Kulon Progo Regency, registered under the Badan Usaha Milik Desa (BUMDes). The analysis method used was SEM-PLS. The study found that the external environment has a non-significant direct influence on organizational performance, but it significantly affects organizational performance when innovation is considered as a mediating variable. This might be due to the industry where the organization operates not being strongly influenced by external environmental factors. Human resource competencies have a significant direct influence on organizational performance, but their influence on organizational performance with innovation as a mediating variable is not significant. The research revealed that despite high levels of human resource competencies and innovation, they are not sufficient to enhance organizational performance. Knowledge management significantly influences organizational performance, both directly and with innovation as a mediating variable. These findings diverge from previous research and suggest that other factors may impact the external environment and organizational performance.